Effective use of flecainide in the treatment of fetal supraventricular tachyarrhythmias - Lemos,Mariana (2022)
Abstract Sustained fetal tachyarrhythmias (most commonly supraventricular fetal tachycardia) can lead to hydrops fetalis and eventual fetal demise if untreated. Although many centers now use flecainide as first-line therapy there is still some controversy. Effectiveness and safety are two major concerns regarding anti-arrhythmic therapy. We describe three cases of fetal supraventricular tachyarrhythmia, one of which presenting with hydrops fetalis, two of them successfully treated with monotherapy flecainide. The third case, an atrial flutter that was initially resistant to sotalol therapy converted to sinus rhythm with combination therapy with flecainide and digoxin after 48 hours. There were no side effects.